2019
DOI: 10.1002/mgg3.1041
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of FBN1 frameshift and nonsense mutations in Marfan syndrome patients with aortic dissection

Abstract: Background: Marfan syndrome (MFS) is an inherited connective tissue disease that mainly involves Fibrillin-1 (FBN1) mutations and aortic manifestations. In this study, we investigated the correlations between the FBN1 genotype-phenotype and aortic events (aortic dissection and aortic aneurysm) in patients with Marfan syndrome. Methods: Genotype and phenotype information was evaluated in 180 patients with MFS. DNA sequencing was performed on each patient. According to the clinical manifestation, these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Other studies confirmed this distribution of variants. Missense variants substituting or creating a cysteine in one of the cbEGF domains (calcium-binding EGF) are the most common [24][25][26][27]. Overall, the distribution of pathogenic variants identified in our cohort is consistent with previous data [28][29][30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other studies confirmed this distribution of variants. Missense variants substituting or creating a cysteine in one of the cbEGF domains (calcium-binding EGF) are the most common [24][25][26][27]. Overall, the distribution of pathogenic variants identified in our cohort is consistent with previous data [28][29][30].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, in HI patients, treatment with losartan appeared to be more efficient [40]. Moreover, Xu et al and Li et al showed a higher rate of aortic dissection in this patient group [22,26]. The causes of these results could be obscured in childhood, as aortic dissection is rare in the young.…”
Section: Cardiovascular Genotype-phenotype Correlationsmentioning
confidence: 79%
“…Similarly, Franken et al (2016) confirmed the worst prognosis in HI patients with 2.4‐fold greater risk for the combined endpoint of aortic dissection and cardiovascular death than DN patients 8 . In a study by Xu et al (2020), frameshift mutations and nonsense mutations were more common in patients with aortic dissection, whereas missense mutations were more common in patients with aortic aneurysm 35 . Supporting this, the pathological study of aortic wall tissue showed that elastic fibers were sparser and more disorganized in patients with frameshift and nonsense mutations than than in peers with missense variants.…”
Section: Discussionmentioning
confidence: 95%
“…The mutation spectrum is composed of nonsense, missense, frameshift, and exon deletion, etc. [ 3 ] Among them, about 90% of MFS patients’ mutation sequence information limited to the coding region and specific splice sites. However, about 10% of patients still cannot identify the genetic cause of the disease [ 1 ].…”
Section: Introductionmentioning
confidence: 99%